Study of Arthropod Communities in A Virginia Tobacco Agro-Ecosystem - Thei, Ruth Stella; Abadi, Abdul Latief; Mudjiono, Gatot; Suprayogo, Didik (Journal of Tropical Life Science, 2013)
The cultivation of tobacco is one of users of agro-chemical substances such as insecticides, herbi-cides, defoliants, and fertilizers among other food crops and plants with high economical value. The use of these chemicals may bring negative effects regarding the richness and abundance of arthropods. The study of arthropod community in the Virginia tobacco ecosystem was carried out in Central Lombok, West Nusa Tenggara Province, during the 2010 plantation year. It was aimed at finding the composition, structure, and dynamic of the arthropod diversity around the tobacco field. Samples were obtained by using trapping techniques (pitfall traps, yellow-pan traps, and sweep net). The number of arthropods found in Virginia tobacco field are 69, consisting of 65 species of insects (belonging to 46 families and 8 orders) and 4 species of spiders (belonging to 4 families). The majority of insects found was Hymenoptera, dominated by bees. Based on the ecological functions, the major group of arthro-pods documented was phytophagous (20 species), mostly Coleoptera and Orthoptera. Yet, the number of predators was relatively more abundant than that of the phytophagous. The number of kinds of ar-thropods commonly interacting around the field fluctuated during the growing period, while in the cultivation period the number decreased. The diversity of the species (H) and the ratio of abundance of the natural enemies and phytophagous in the field was high.